First evaluation of associated gut microbiota in wild thick-lipped grey mullets (Chelon labrosus, Risso 1827) - García-Márquez, Jorge; Cerezo Ortega, Isabel M.; López Figueroa, Félix; Abdala-Díaz, Roberto Teófilo; Arijo-Andrade, Salvador (My University, 2022)
The need for species diversification in Mediterranean aquaculture has promoted the culture of omnivorous and herbivorous species. Within this context, it is worth noting the high potential presented by the species of the family Mugilidae (mullets), which is considered a priority within the current strategies of European aquaculture (Alexander et al. 2015). One of the mullets with potential for use in aquaculture is the thick-lipped grey mullet (Chelon labrosus), due to its great adaptability to different culture conditions, omnivorous profile, high osmoregulatory capacity, and resistance to environmental variations (Pujante et al., 2018). However, there is a lack of information regarding the composition and functions of its intestinal microbiota. Documenting the bacteria present in healthy individuals is the first step to understanding the impacts of microbial manipulation in aquaculture systems (Tarnecki et al., 2016). In this sense, the knowledge of bacterial diversity from healthy wild fish in their natural environment is essential. Furthermore, the study of the functionality of the intestinal microbiota of wild fish provides information on its capacity to adapt to different culture conditions. Thus, this study aimed to characterize the intestinal microbiota of wild C. labrosus and explore its potential functionality on the host. Predicted functions of intestinal microbiota showed the most abundant those related to amino acid metabolism, carbohydrate metabolism, energy metabolism, membrane transport, and cell replication and repair. Furthermore, the analysis revealed microbial functional genes related to the elimination of environmental toxins. These functions of intestinal microbiota might provide beneficial effects for the host.
Keywords: Salmonetes - acuicultura; Microbiota; Mugílidos; Chelon labrosus; Acuicultura